Implementasi Kebijakan Dinas Pendidikan Kebudayaan Pemuda dan Olahraga dalam Meningkatkan Mutu Guru di SMP Kecamatan Bula Kabupaten Seram Bagian Timur - Muh. Ali Kilbaren; R. Kempa; Sumarni Rumfot (LP. Ma'arif Janggan Magetan, 2024)
Policy implementation in principle is a way for a policy to achieve its goals. The implementation process will vary depending on the nature of the policy being implemented. Different decisions will show the characteristics, structures and relationships between the factors that influence the implementation of public policy so that the implementation process will also experience differences. The characteristics of education policy include (1) having goals, (2) having formal legal aspects, (3) having operational concepts. Compiled by the authorities, the formulator has capacity in the field of education, can be measured and evaluated, has a systematic formulation, and is prioritized. Policy implementation is seen in a broad sense, which is the stage of the policy process immediately after the enactment of the law. Implementation is seen broadly as having the meaning of implementing laws in which various actors, organizations, procedures and techniques work together to carry out policies in an effort to achieve the goals of policies or programs. Implementation of school quality assurance is a government policy to improve the quality of education. Implementation of a quality assurance system in primary and secondary education refers to standards according to applicable regulations. The results of the study show that the planned policies related to aspects of quality improvement do not indicate the direction and targets that must be achieved, this is due to the techniques and strategies in the formulation of policies related to programs that show a focus on solving educational problems related to quality. The quality of education is influenced by the competence of teachers while the academic qualifications of teachers are at the secondary school level (97.0%) for elementary schools (69.4%) for elementary schools (38.6%) for S1. For the level of certification (PAUD has been certified 0% - not yet certified 99.5%) School (Elementary has been certified 6.8% - has not been certified 93.2%) and Secondary Education (certified 8.3% and not yet certified 91.7 %).